The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1137/040613378
|View full text |Cite
|
Sign up to set email alerts
|

A New Notion of Weighted Centers for Semidefinite Programming

Abstract: The notion of weighted centers is essential in V-space interior-point algorithms for linear programming. Although there were some successes in generalizing this notion to semidefinite programming via weighted center equations, we still do not have a generalization that preserves two important properties-(1) each choice of weights uniquely determines a pair of primal-dual weighted centers, and (2) the set of all primal-dual weighted centers completely fills up the relative interior of the primal-dual feasible r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 22 publications
(27 reference statements)
0
14
0
Order By: Relevance
“…Concerning the second subject, we have already obtained a partial result in the proof of (iii) of Theorem 5.5. As a related result, we should refer to Chua's work [3] for homogeneous conic programming: The author showed that the paths defined by a class of optimal barriers converge to analytical centers of optimal faces whenever the primal-dual pair of problems has strictly complementarity solutions.…”
Section: A Homogeneous Model For the Cpmentioning
confidence: 96%
See 1 more Smart Citation
“…Concerning the second subject, we have already obtained a partial result in the proof of (iii) of Theorem 5.5. As a related result, we should refer to Chua's work [3] for homogeneous conic programming: The author showed that the paths defined by a class of optimal barriers converge to analytical centers of optimal faces whenever the primal-dual pair of problems has strictly complementarity solutions.…”
Section: A Homogeneous Model For the Cpmentioning
confidence: 96%
“…It is known that the self-scaled cones associated with the self-scaled barriers are closely related to the symmetric cones [1,10,11,27]. See also [15,7,23,28,25,24,3] for other extensions of primal-dual methods to the positive semidefinite cones, the symmetric cones, the self-scaled cones, or the homogeneous cones.…”
mentioning
confidence: 97%
“…Hence, in this section, we consider the relation between the standard central paths for SDP and weighted central paths given by the weighted barriers. (See [3] for some convergence properties of these weighted central paths. )…”
Section: Neighbourhoods Of the Weighted Central Pathsmentioning
confidence: 99%
“…Such paths have been studied in [11,17,20,22]. The paper [5] also proposes a definition of paths which requires a Cholesky factorization in addition to the algebraic equations (2).…”
mentioning
confidence: 99%